10.6 Influence of prenatal adenovirus-VEGF gene therapy on mRNA expression of angiogenic related genes in fetal and postnatal ovine intestine. (9th June 2014) - Jia, GQ; Haring, JS; Aitken, RP; Milne, JS; Carr, DJ; David, AL; Wallace, JM; Caton, JS
Abstract : Maternal uterine artery adenovirus VEGF (Ad. VEGF-A165 ) gene therapy has increased pre- and early postnatal growth velocity in an overnourished adolescent ovine model of fetal growth restriction. Our objective was to investigate effects of prenatal Ad. VEGF on fetal and postnatal intestinal mRNA expression of angiogenic factors and receptors (n = 18 genes). In Exp. 1, first parity ewe lamb recipients were offered a control (CON; n = 12) or high (H; n = 45, 2 x CON) quantity of the same diet after singleton embryo transfer. At 89 ± 1.5d of gestation overnourished H-ewes were randomly allocated to receive 1 of 3 injections into both uterine arteries: a) Ad. VEGF-A165 (5 × 10 11 particles; n = 17); b) control Ad vector containing the β-galactosidase reporter gene, Ad. LacZ (n = 14); c) saline (n = 14). CON received saline. In Exp. 2, overnourished ewes received no injection (n = 6), Ad. VEGF-A165 (n = 16) or saline (n = 15). Ewes lambed normally at 141 ± 0.4d gestation. Fetal (d130) and postnatal (d84) intestinal tissues were harvested and mRNA expression relative to 18s determined. In Exp. 1, no differences ( P ≥ 0.16) were observed in mRNA expression. In Exp. 2, maternal Ad. VEGF-A165 increased ( P ≤ 0.04) mRNA expression of FLT1, KDR, NRP1, FGF2R, TIE2, NOS3, and sGC, and tended ( P ≤ 0.10) to increase ANG1, ANG2, NRP2, FGF2, and HIF1A . Thus, previously reported benefits of this prenatal therapy on birth weight and early postnatal growth were mirrored by increased expression of angiogenic genes. These may in turn influence intestinal vascularity and thereby absorptive capacity. (Wellcome Trust UK, Scottish Government, and USDA-AFRI Grant 2012–67016–1945; Presented previously; Aspen/Snowmass Perinatal Biology Symposium August 24–27, 2013).